Sosialisasi Cek Tekanan Darah Rumah (CERAMAH) Di Desa Cot Masam Kuta Baro Aceh Besar - Yadi Putra; Fauziah Fauziah; Urip Pramata; Nanda Desreza; Syifa Karmila (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
High blood pressure is the most common public health problem. Uncontrolled blood pressure can lead to complications, blood pressure is the highest disease in Aceh Besar district, especially Kuta Baro District and Cot Masa village is one of them. This community service activity was carried out in Cot Masam village, precisely at the community house on August 10, 2022. The purpose of this community service is to foster community knowledge about checking blood pressure at home in order to avoid the dangers of hypertension. The results of community service obtained an increase in knowledge from the pre-test results of 1.20% increased in the post-test results, namely 1.50%. Therefore it is recommended that people routinely check blood pressure in their respective homes.